2020
DOI: 10.1021/acsabm.0c00780
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Delivery of 5-Fluorouracil to Human Colon Cancer Cells Using Multifunctional Arginine-Coated Manganese Oxide Nanocuboids with MRI Properties

Abstract: 5-Fluorouracil (5-FU) is one of the most prescribed drugs and the major component of chemotherapy for the treatment of colorectal cancer. In this study, we have designed arginine-functionalized manganese oxide nanocuboids (Arg@MNCs) for the effective delivery of 5-FU to colon cancer cells. Arginine was used as multifunctional agent to provide stability to MNCs, achieve high drug loading, control the release of loaded drug, and improve delivery to cancer cells. The synthesized Arg@MNCs were characterized by DLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Mn 2+ - based imaging agents are considered to have ideal characteristics for MRI because of their ability to overcome toxicity issues, short circulation half-life, and low intracellular accumulation that other T1 contrast agents suffer [ 50 ]. Manganese oxide (MnO) and other materials displayed negligible toxicity and good T1 weighted contrast effects and has been used as preclinical in vivo T1 agents [ 51 53 ]. However, it was revealed that the geometry and morphology of MnO nanomaterials critically affects their relaxivity, since the interaction with water strongly influences contrast effects [ 54 ].…”
Section: Biomedical Imaging Used For In Vivo Pharmaceutical Evaluatio...mentioning
confidence: 99%
“…Mn 2+ - based imaging agents are considered to have ideal characteristics for MRI because of their ability to overcome toxicity issues, short circulation half-life, and low intracellular accumulation that other T1 contrast agents suffer [ 50 ]. Manganese oxide (MnO) and other materials displayed negligible toxicity and good T1 weighted contrast effects and has been used as preclinical in vivo T1 agents [ 51 53 ]. However, it was revealed that the geometry and morphology of MnO nanomaterials critically affects their relaxivity, since the interaction with water strongly influences contrast effects [ 54 ].…”
Section: Biomedical Imaging Used For In Vivo Pharmaceutical Evaluatio...mentioning
confidence: 99%
“…3 ). [31] Therefore, the lipophilic cation exchanger within the membrane phase can likely interact with the arginine in the peptide and leads to the accumulation and even extraction of the MBspeptide into the polymeric membrane.…”
Section: Confirmation Of the Ion-pair Formation In Membranementioning
confidence: 99%
“…Apart from biocompatibility, the GNRs exhibit a highly efficient photothermal conversion, which enabled the chemophotothermal therapy on CRC cells through functionalization with anticancer drugs (Zhou et al, 2017). In another study, manganese-based (Mn) NPs stabilized by L-arginine were developed as a nanocarrier system to deliver 5-FU to colon cancer cell lines (Jain et al, 2020). In that case, cell viability was significantly reduced after the treatment with 5-FU-loaded Mn-based NPs as compared to the treatment with free 5-FU, being twice lower in the former specimen group than in the latter.…”
Section: Nanomedicines and Colorectal Cancermentioning
confidence: 99%